2020
DOI: 10.3390/genes11111250
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Subtype-Phenotype Analysis of Growth Hormone Treatment on Psychiatric Behavior in Prader-Willi Syndrome

Abstract: Prader-Willi syndrome (PWS) is a complex multisystemic condition caused by a lack of paternal expression of imprinted genes from the 15q11.2–q13 region. Limited literature exists on the association between molecular classes, growth hormone use, and the prevalence of psychiatric phenotypes in PWS. In this study, we analyzed nine psychiatric phenotypes (depressed mood, anxiety, skin picking, nail picking, compulsive counting, compulsive ordering, plays with strings, visual hallucinations, and delusions) recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In particular, patients with UPD are more likely to have higher rates of behavioral problems in comparison to the deletion or imprinting subtypes. [3] Importantly, it is notable that this same abnormalitythat is, UPDprovides a better prognosis when it comes to language development and intellect. [4,5] This relative protection from severe intellectual dysfunction, and in particular Amon's preserved language development, is a biological protective factor and tends to preserve a pattern of higher academic achievement.…”
Section: Putting Things Togethermentioning
confidence: 99%
“…In particular, patients with UPD are more likely to have higher rates of behavioral problems in comparison to the deletion or imprinting subtypes. [3] Importantly, it is notable that this same abnormalitythat is, UPDprovides a better prognosis when it comes to language development and intellect. [4,5] This relative protection from severe intellectual dysfunction, and in particular Amon's preserved language development, is a biological protective factor and tends to preserve a pattern of higher academic achievement.…”
Section: Putting Things Togethermentioning
confidence: 99%
“…Dobrescu et al 13 found no differences between the deletion and UPD types in specific facial features, hypopigmentation, sleep disorder, obesity, and scoliosis, though they only had a total of 35 individuals with PWS in that study. Montes et al 14 found that patients with deletion type were more prone to skin picking, while patients with UPD showed a higher incidence of anxiety, especially after growth hormone therapy. However, there were no differences in other behavioral abnormalities, such as depression, nail biting, compulsive disorder, or visual hallucinations.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the youth with PWS had increased spine bone mineral content following physical activity interventions; however, bone remodeling markers remained unaltered. Montes et al [ 14 ] reported on genetic subtype–phenotype analysis in PWS while individuals were on growth hormone treatment and examined their psychiatric behavior. They found that skin picking was more frequent in those with the chromosome 15q11-q13 deletion compared to non-deletion (maternal disomy 15), while anxiety was more common in those with maternal disomy compared to the deletion.…”
mentioning
confidence: 99%